Primary care clinician antibiotic prescribing decisions in consultations for children with RTIs: a qualitative interview study - Horwood, Jeremy (Br J Gen Pract, 2016)
BACKGROUND: Respiratory tract infections (RTIs) are a major primary care challenge in children because they are common and costly, there is uncertainty regarding their diagnosis, prognosis, and management, and the overuse of antibiotics leads to illness medicalisation and bacterial resistance. AIM: To investigate healthcare professional (HCP) diagnostic and antibiotic prescribing decisions for children with RTIs. DESIGN AND SETTING: Semi-structured interviews conducted with 22 GPs and six nurses. HCPs were recruited from six general practices and one walk-in centre, serving a mix of deprived and affluent areas. METHOD: Interviews were audiorecorded, transcribed, imported into NVivo 9, and analysed thematically. RESULTS: HCPs varied in the symptom and clinical examination findings used to identify children they thought might benefit from antibiotics. Their diagnostic reasoning and assessment of perceived clinical need for antibiotics used a dual process, combining an initial rapid assessment with subsequent detailed deductive reasoning. HCPs reported confidence diagnosing and managing most minor and severe RTIs. However, residual prognostic uncertainty, particularly for the intermediate illness severity group, frequently led to antibiotic prescribing to mitigate the perceived risk of subsequent illness deterioration. Some HCPs perceived a need for more paediatrics training to aid treatment decisions. The study also identified a number of non-clinical factors influencing prescribing. CONCLUSION: Prognostic uncertainty remains an important driver of HCPs’ antibiotic prescribing. Experience and training in recognising severe RTIs, together with more evidence to help HCPs identify the children at risk of future illness deterioration, may support HCPs’ identification of the children most and least likely to benefit from antibiotics.